2017
DOI: 10.1111/dme.13527
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretory defect in familial partial lipodystrophy Type 2 and successful long-term treatment with a glucagon-like peptide 1 receptor agonist

Abstract: Background Familial partial lipodystrophies are rare monogenic disorders that are often associated with diabetes. In such cases, it can be difficult to achieve glycaemic control.Case report We report a 34-year old woman with familial partial lipodystrophy type 2 (Dunnigan) and diabetes; her hyperglycaemia persisted despite metformin treatment. A combined intravenous glucose tolerance-euglycaemic clamp test showed severe insulin resistance, as expected, but also showed strongly diminished first-phase insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…Conventional and intensified antidiabetic treatment failed to normalize glycemic control but the introduction of metreleptin resulted in a drastic improvement of glycemic control and plasma triglycerides. Research data regarding the use of glucagon-like-peptide-1 (GLP-1) agonists in patients with lipodystrophy are scarce and their effect has been described only in case reports (21,22). Contrary to our case, in these previous reports authors pointed out that these regimens resulted in improvement of glycemic control and in reduction of insulin requirements, suggesting the positive effect of GLP-1 analogues in the management of diabetes in lipodystrophy syndromes (21,22).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Conventional and intensified antidiabetic treatment failed to normalize glycemic control but the introduction of metreleptin resulted in a drastic improvement of glycemic control and plasma triglycerides. Research data regarding the use of glucagon-like-peptide-1 (GLP-1) agonists in patients with lipodystrophy are scarce and their effect has been described only in case reports (21,22). Contrary to our case, in these previous reports authors pointed out that these regimens resulted in improvement of glycemic control and in reduction of insulin requirements, suggesting the positive effect of GLP-1 analogues in the management of diabetes in lipodystrophy syndromes (21,22).…”
Section: Discussioncontrasting
confidence: 82%
“…Research data regarding the use of glucagon-like-peptide-1(GLP-1) agonists in patients with lipodystrophy are scarce and their effect has been described only in case reports ( 21 , 22 ). Contrary to our case, in these previous reports authors pointed out that these regimens resulted in improvement of glycemic control and in reduction of insulin requirements, suggesting the positive effect of GLP-1 analogues in the management of diabetes in lipodystrophy syndromes ( 21 , 22 ). It is noteworthy to mention that there is a concern regarding the use of GLP-1 analogues in patients with lipodystrophy and high TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is the first-line therapy although some patients may require additional agents including high doses of insulin. In individual patients with FPLD insulin secretion disruption [49] or low dipeptidyl peptidase 4 (DPP4) levels were observed in addition to insulin resistance, suggesting the use of glucagon-like peptide 1 receptor agonists (GLP1) [50] to improve glycemic control and reduce the high insulin demand. However, no studies in the other forms of lipodystrophy have yet been conducted [51].…”
Section: Therapeutic Approaches For Lipodystrophymentioning
confidence: 99%
“…The use of a combined intravenous glucose tolerance-euglycemic clamp in cases of FPLD revealed not only increased insulin resistance but also impaired first-phase insulin secretion. 77 In addition, Valerio et al 78 showed that the increased visceral adiposity characterizing FPLD is directly related to low dipeptidyl peptidase 4 (DPP4) levels. The above observations led researchers to investigate the role of glucagon-like peptide 1 receptor agonists (GLP1 Ras) in the management of overt diabetes in FPLD cases with promising results such as improvement of glycemic control and reduced insulin requirements.…”
Section: Treatmentmentioning
confidence: 99%
“…The above observations led researchers to investigate the role of glucagon-like peptide 1 receptor agonists (GLP1 Ras) in the management of overt diabetes in FPLD cases with promising results such as improvement of glycemic control and reduced insulin requirements. 77,79 The sodium-glucose co-transporter 2 (SGLT2) inhibitors have an insulin-independent effect on glucose control and have been proven to be beneficial in cardiovascular and renal disease in type 2 diabetes mellitus. Evidence from cases of congenital generalized lipodystrophy has showed that use of SGLT2 inhibitors is associated with improvement in all metabolic markers and reduced incidence of cardiomyopathy.…”
Section: Treatmentmentioning
confidence: 99%